Efektivitas Susu Kedelai Murni (Glycine max (L.) Merill) Sebagai Alternatif Bahan Remineralisasi Gigi - Mona, Deli (Majalah Kedokteran Andalas, 2023)
Objective: to determine the effectiveness of pure soy milk (Glycine max (L.) Merill) as an alternative tooth remineralization material. Methods: by collecting and reviewing various journals, literature reviews, and books on soy milk, calcium, remineralization, and demineralization of teeth. Literature review is done by looking for similarities, dissimilarities, providing views, comparing, and concluding from the journals obtained. Results: Remineralization can occur due to the presence of sufficient Ca2+ and PO4 3- ions so that these ions can diffuse into the tooth surface and rebuilding of soluble hydroxyapatite crystals occurs so that it can increase the hardness of the tooth surface. Conclusion: calcium and phosphorus contained in soy milk (Glycine max (L.) Merill) are effective for increasing tooth remineralization with an indicator of an increase in the surface hardness of tooth enamel.Â